2008
DOI: 10.1513/pats.200807-071th
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Injury and Repair in Chronic Obstructive Pulmonary Disease

Abstract: Cardiovascular disease represents a considerable burden in terms of both morbidity and mortality in patients with chronic obstructive pulmonary disease (COPD). For 20 years, forced expiratory volume in 1 second (FEV 1 ) has been an established predictor of cardiovascular mortality among smokers, never-smokers, and patients with COPD. We review evidence for increased cardiovascular risk in COPD. In addition, we assess the emerging evidence which suggests that hypoxia, systemic inflammation, and oxidative stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
0
13

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 145 publications
7
75
0
13
Order By: Relevance
“…These have been the subject of multiple review articles and a detailed discussion is beyond the scope of this report (5,33). Among these increased arterial stiffness and systemic inflammation are worthy of brief mention here.…”
Section: Discussionmentioning
confidence: 99%
“…These have been the subject of multiple review articles and a detailed discussion is beyond the scope of this report (5,33). Among these increased arterial stiffness and systemic inflammation are worthy of brief mention here.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there may be other underlying mechanisms, such as oxidative stress. 25 Clinical and experimental studies have shown that the production of reactive oxygen species (ROS) is increased in COPD patients by inhalation of toxic substances, [26][27][28] and that the antioxidative system in these patients is impaired, 29 leading to a state of high oxidative stress. After such an increase in ROS production, the spillover of ROS from the lung could lead to systemically increased levels of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…COPD is currently considered as a systemic disorder that is associated with an increased risk of diabetes mellitus, hypertension, and cardiovascular disease [an independent risk factor] [2,3]. The suggested mechanisms for these associations include hypoxia, oxidative stress, and systemic inflammation in COPD [4,5].…”
Section: Introductionmentioning
confidence: 99%